Questioning the Authority of Converts' Preaching: A Critical Discourse Analysis of Sidogiri Media Edition 211 - Muhammad Hafid Yasuli; Siti Raudhatul Jannah; Kun Wazis (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to analyze how Sidogiri Media, as a pesantren media, represents the discourse of the authority of converts' da'wah in its 211th edition entitled